2007
DOI: 10.1111/j.1600-0536.2007.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch test reactivity to a cobalt–chromium–molybdenum alloy and stainless steel in metal‐allergic patients in correlation to the metal ion release

Abstract: Nickel, chromium, and cobalt released from stainless steel and CoCrMo alloys have been postulated to trigger hypersensitivity reactions. The objective of this study was to assess the ion release from a CoCrMo alloy and stainless steel in vitro and the cutaneous reactivity to it by patch test. 52 metal-allergic patients and 48 non-allergic controls were patch tested to stainless steel and CoCrMo discs. In addition, using atomic absorption spectrometry, the release of nickel, cobalt, and chromium from both mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 30 publications
5
29
0
8
Order By: Relevance
“…In spite of the high resistance to corrosion of the alloys used for their manufacture, they may still suffer some localized corrosion resulting from the oral cavity conditions . It has been shown that orthodontic apparatus release metallic ions into the tissues and fluids of patients wearing them, including blood and urine (Summer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the high resistance to corrosion of the alloys used for their manufacture, they may still suffer some localized corrosion resulting from the oral cavity conditions . It has been shown that orthodontic apparatus release metallic ions into the tissues and fluids of patients wearing them, including blood and urine (Summer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For hand applications the irritation of overlying free gliding tendons in contact with the plate is also of concern (Nazzal et al, 2006). Furthermore, the negative influence of metal ions and salts on adjacent tissues and organs is well documented (Case et al, 1994: Kasai et al, 2003: Keegan et al, 2007Summer et al, 2007). Device extraction in children can further cloud the matter (Rosson and Shearer, 1991;Kahle, 1994;Alzahrani et al, 2003;Kim et al, 2005;Peterson, 2005;Busam et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that subsequent to fulfilling its function a device can negatively affect the host giving rise to complications such as delayed infections (Highland and LaMont, 1985;Emel et al, 2007), allergic reactions (Summer et al, 2007), implant loosening or breakage , device migration (Seipel et al, 2001) and hindrance of skeletal growth (Togrul et al, 2005). For hand applications the irritation of overlying free gliding tendons in contact with the plate is also of concern (Nazzal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Specific immunologic mechanisms (such as delayed-type hypersensitivity) may at best play a role in a small minority of patients. 32 If skin patch testing accurately recreated the immunologic environment of internal periprosthetic tissue, then one would expect a much higher percentage of metal-sensitive patients in this study to react to these metal test discs. It has been shown that particulate and soluble debris derived from Cobalt-Chromium-Molybdenum alloy implants can (in an immunologically nonspecific manner) induce monocyte-macrophage activation and secretion of proinflammatory cytokines.…”
mentioning
confidence: 79%